Analisis Peran Hukum Pidana Dalam Penanganan Tindak Pidana Ekonomi Melalui Evaluasi Regulasi Dan Praktik - Henry Afrillo; Hudi Yusuf (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
In an increasingly interconnected era of globalization, the dynamics of the economy present significant challenges in the legal aspect, particularly regarding economic crimes. The rapid development of technology has exacerbated the complexity of illegal actions, ranging from market manipulation to abuse of power in the financial sector. The existence of strong legal regulations and an effective law enforcement system has become crucial to protect society and maintain economic stability. In the context of Indonesian law, the role of criminal law in addressing economic crimes is essential, referring to the principle of social justice embedded in the 1945 Constitution. However, the implementation of these regulations faces various obstacles, including limited resources and suboptimal coordination among institutions. This study aims to evaluate the effectiveness of existing criminal law regulations, identify obstacles in their implementation, and formulate innovative steps to improve law enforcement in handling economic crimes. The method used is qualitative research with document analysis and case studies. Through the collection and analysis of legal documents, case reports, and case studies, this study aims to examine how well current regulations can anticipate the development of increasingly complex economic crime modus operandi. The analysis results show that although regulations are in place, there are shortcomings in implementation and law enforcement, as well as an urgent need to update regulations to keep pace with the challenges of technology and globalization. Therefore, this study suggests the need for ongoing legal reforms, enhanced capacity for law enforcement institutions, and the development of policies based on empirical data and technology to enhance the efficiency of law enforcement in addressing economic crimes. It is also necessary to raise public legal awareness and foster partnership between the public and private sectors to establish a responsive and highly-integrated legal system to face increasingly sophisticated economic crimes.